Facile Fabrication of AIE‐Active Fluorescent Polymeric Nanoparticles with Ultra‐Low Critical Micelle Concentration Based on Ce(IV) Redox Polymerization for Biological Imaging Applications. Issue 8 (21st February 2017) - Wan, Qing; Xu, Dazhuang; Mao, Liucheng; He, Ziyang; Zeng, Guangjian; Shi, Yingge; Deng, Fengjie; Liu, Meiying; Zhang, Xiaoyong; Wei, Yen
Abstract : Luminescent organic nanoparticles (LONs) with aggregation‐induced emission (AIE) features and ultralow critical micelle concentrations have been fabricated via Ce(IV) redox polymerization. This strategy is very simple, effective, and can be potentially extended for fabrication of many other AIE‐active LONs. The resultant AIE‐active LONs possess many attractive physicochemical properties and are of great potential for biomedical applications. Abstract : Fluorescent polymeric nanoparticles (FPNs) with aggregation‐induced emission (AIE) property have received increasing attention and possess promising biomedical application potential in the recent years. Many efforts have been devoted to the fabrication methodologies of FPNs and significant advance has been achieved. In this contribution, a novel strategy for the fabrication of AIE‐active amphiphilic copolymers is reported for the first time based on the Ce(IV) redox polymerization. As an example, ene group containing AIE‐active dye (named as Phe‐alc) is directly grafted onto a water soluble polymer polyethylene glycol (PEG) in H2 O/THF system under low temperature. Thus‐obtained amphiphilic fluorescent polymers will self‐assemble into FPNs with ultra‐low critical micelle concentration, ultra‐brightness, and great water dispersibility. Biological evaluation results suggest that the PEG‐poly(Phe‐alc) possess excellent biocompatibility and can be used for tracing their behavior in cells using confocal laser scanning microscope. These features make PEG‐poly(Phe‐alc) FPNs promising candidates for many biomedical applications, such as cell imaging, drug delivery vehicles, and targeted tracing. More importantly, many other functional groups can also be incorporated into these AIE‐active FPNs through the redox polymerization. Therefore, the redox polymerization should be a facile and effective strategy for fabrication of AIE‐active FPNs.